Alterantes microbianos atípicos en yogures argentinos: mohos gasógenos y bacterias del género Gluconobacter - Capra, María Luján (2021)
Microbial food alterations lead to unfit products for consumption, and their discarding, to significant economic losses for the food industry. During storage, fresh foods offer available niches for the survival and growth of undesirable microorganisms. In dairy products, data regarding spoilage and/or pathogenic bacteria is better documented than those for molds and yeasts. Dairy products are less susceptible to mold's contamination than products such as fruits and vegetables, due to their refrigerated storage; their elaboration from heat-treated milk and, for fermented ones, the dominant microbiota that acidifies the medium. However, even cheeses and yogurts may be susceptible to mold contamination. Atypical cases of yogurt samples containing spoilage microorganisms not previously reported (molds producing gas and bacteria of the genus Gluconobacter) in Argentinean fermented milks are presented here. For yogurt, in particular, the “classic” altering organisms were always being yeasts, and in other countries, molds belonging to the genus Aspergillus.